2015
DOI: 10.1515/chem-2015-0149
|View full text |Cite
|
Sign up to set email alerts
|

New feed supplement from macroalgae as the dietary source of microelements for pigs

Abstract: Abstract:The aim of the study was to perform feeding experiments on growing pigs in order to assess the impact of macroalga Enteromorpha sp. enriched with Zn(II) and Cu(II) ions via the biosorption process on the mineral composition of blood, meat, liver, feces and urine. In the control group, microelements were supplemented as inorganic salts, whereas in the experimental groups they were replaced by enriched macroalga. After 3 months of the feeding experiment, it was found that the meat was biofortified with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 33 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…Alternative protein supplements with adequate nutritional values and bioavailability include single cell protein (SCP), processed vegetable protein, and insect protein ( Kim et al, 2019 ). The SCP, including yeast, microalgae, and bacterial cells, contains high levels amino acids (AA), fats, and vitamins ( Kihlberg, 1972 ; Michalak et al, 2015 ; Lopes et al, 2017 ). However, intact SCP supplemented in animal diets may cause reduced growth performance, intestinal health, and nutrient digestibility due to indigestible cell wall ( Rumsey et al, 1991 ; Zhang et al, 2013 ; Cruz et al, 2020 ) and the potential endogenous toxins ( Farstad, 1977 ) reducing nutrient digestibility and causing intestinal challenges to young pigs ( Kim et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Alternative protein supplements with adequate nutritional values and bioavailability include single cell protein (SCP), processed vegetable protein, and insect protein ( Kim et al, 2019 ). The SCP, including yeast, microalgae, and bacterial cells, contains high levels amino acids (AA), fats, and vitamins ( Kihlberg, 1972 ; Michalak et al, 2015 ; Lopes et al, 2017 ). However, intact SCP supplemented in animal diets may cause reduced growth performance, intestinal health, and nutrient digestibility due to indigestible cell wall ( Rumsey et al, 1991 ; Zhang et al, 2013 ; Cruz et al, 2020 ) and the potential endogenous toxins ( Farstad, 1977 ) reducing nutrient digestibility and causing intestinal challenges to young pigs ( Kim et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides beneficial chemical composition, Cladophora glomerata might be enriched with various minerals by the biosorption process, which increases its nutritional value and therapeutic properties. Biosorption is a process of passive sorption and complexation of particular sorbents including ions such as Cr(III), that besides their sorbent properties also become valuable nutrients [ 23 , 24 ]. Thus, the combination of biosorption, with particular of Cr(III) ions together with high content of antioxidants as well as anti-inflammatory compounds, might be a beneficial future diet for EMS treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was not the case of Sulphur, which was at least 47% higher in seaweed diets. Several authors have previously reported that seaweeds are a good source of microelements, but such an effect on hepatic Sulphur content has not been reported 47 . Accordingly, Copper and Manganese were significantly reduced in L. digitata with or without the recombinant alginate lyase compared to control, and also in L. digitata with the recombinant alginate lyase compared to L. digitata alone.…”
Section: Discussionmentioning
confidence: 97%